A Relação com o Saber de diretores: situações de conflitos e violências escolares - Morito, Jéssica Veloso (Universidade Federal de São Carlos, 2023)
The discussion on violence in the school environment focuses on understanding what the cycles of violence(s) are, in such a way that it provides a welcoming space in the consolidation of welcoming so that the school body, first of all, wants to be in that place to that afterwards, seek a quality education for their students. From this premise, the objective of this research is to analyze the principals' knowledge in relation to school violence. For this, the speeches of school directors were analyzed - through the transcription of the recordings of the meetings by Google Meet - from 10 Brazilian states, who made up a group of professionals who participated in the training course in mentoring directors carried out in partnership between the Federal University of São Carlos (UFSCar) and the Secretariat of Basic Education of the Ministry of Education (SEB/MEC). Complementarily, the research problem is how do principals deal with violence at school? The theoretical foundation is punctuated in the knowledge of the school directors in the perspective of the theory of the Relation with Knowledge (RcS) of Bernard Charlot (2000). The methodology used was qualitative research with an exploratory approach, based on the analysis of the sayings and reflective activities carried out by these directors, with a clipping of one of the thematic rooms of the course called “Social and school violence: the challenge of everyday relationships”. It was concluded that there was an ease in recognizing spaces with situations of explicit violences, however, at the same time, there was a difficulty, on the part of the researched directors, in identifying moments of protagonism in these same areas. Future studies are indicated in order to follow more closely the panorama of violence in the new social configurations that enter the walls of schools and the practices of these directors in different regions of Brazil, mainly due to the diversity of Brazilian schools.
The Relationship with the Knowledge of principals: situations of conflict and school violence
La Relación con el Saber de los directores: situaciones de conflicto y violencia escolar
Keywords: Conflitos; Violência; Mentoria de diretores de escola; Saberes de diretores escolares; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO